Hydrogen adsorption on single walled carbon nanotubes-tungsten trioxide composite. (5th October 2017) - Silambarasan, D.; Surya, V.J.; Vasu, V.; Iyakutti, K.; Ravindran, T.R.; Jeyanthinath, M.
Abstract: In this work, hydrogen storage property of single walled carbon nanotubes-tungsten trioxide (SWCNTs-WO3 ) composite is investigated. The composite is prepared and hydrogenated by electron beam (e-beam) evaporation technique. Hydrogenation is carried out during the preparation of the composite itself. The amount of hydrogen uptake by the composite is 2.7 wt%, which is due to the collective adsorption of hydrogen by CNTs and WO3 nanostructured materials, the method of preparation and hydrogenation involved. The incorporated hydrogen is completely (100%) released in the temperature range of 175–305 °C which in turn infers that the hydrogenated composite is stable at room temperature. The stored hydrogen has the average binding energy of 0.4 eV and the nature of binding is found to be weak chemisorption. Spillover mechanism is attributed for the hydrogen uptake of the composite. Graphical abstract: Figure shows the Raman spectra of SWCNTs (C), SWCNTs-WO3 (C-W) and hydrogenated SWCNTs-WO3 (H(C-W)) composite materials. Highlights: Hydrogen storage in SWCNTs-WO3 composite is made by e-beam technique. Preparation and hydrogenation of composite has been done simultaneously. Hydrogen uptake is found to be 2.7 wt% and the system is stable at RT. The system exhibits 100% desorption in the temperature range of 175–305 °C. The nature of binding of hydrogen is found to be weak chemisorption.